National yearly cost of breast cancer screening in the USA and projected cost of advocated guidelines: a simulation study with life table modelling - Martin Eklund; Kimberly Badal; James Staib; Jeffrey A. Tice; Mi-Ok Kim; Leslie Wilson; Stacey Dacosta Byfield; Kierstin Catlett; Liz Maffey; Rashna Soonavala; Yiwey Shieh; Laura J. Esserman (BMJ Open)
Objective The aim of this study was to estimate the total national direct cost of breast cancer screening from 2019 to 2022 and project the total national cost and average lifetime cost of screening per woman for three current guidelines.Design We estimated the national cost of screening from 2019 to 2022, and per cancer detected in 2022, using real-world data on the number of mammograms performed per year. We also projected the national cost of screening using life table modelling for three guidelines: 2021/2023 American College of Radiology (ACR), 2023 American Cancer Society (ACS) and 2024 United States Preventative Services Task Force (USPSTF). The average lifetime cost to screen one woman until age 74 years with each guideline was also estimated. The Optum Labs Data Warehouse was used to estimate commercial and Medicare costs and recall rates. Sensitivity analyses were used to estimate uncertainty and determine which inputs had the largest impact on total national costs.Setting This study was conducted for the USA.Participants Women eligible for breast cancer screening.Interventions Digital mammograms (2D) or digital breast tomosynthesis (3D) and/or MRI.Primary outcome measure Total national cost of screening calculated as the sum of screening and recall costs. Average lifetime cost of screening per woman until 74 years.Results Nationally, screening cost approximately US$11 billion (B) per year from 2019 to 2022 with approximately 37% of eligible women screened each year. In 2022, screening cost US$55 471 per 3D-detected and US$44 000 per 2D-detected invasive or ductal carcinoma in situ case. Using target yearly participation rates of 54%–78% by age of women, the projected cost of screening was US$30B for ACR, US$18B for ACS and US$8B for USPSTF guidelines. The average lifetime cost to screen an average-risk woman was: US$13 416 for ACR, US$7946 for ACS and US$6931 for USPSTF. Participation rates, the proportion of women with a lifetime risk>20% and commercial MRI and 3D costs had the largest impact on total costs.Conclusion The cost of screening varies significantly by guideline (US$8B–US$30B) and was most influenced by participation rates, high-risk population proportions and technology costs. Future work can investigate whether risk-based screening strategies being tested in ongoing clinical trials can reduce national screening costs while improving outcomes.Cite Now